1989
DOI: 10.1017/s0142716400008493
|View full text |Cite
|
Sign up to set email alerts
|

The measurement of bilingualism and its relationship to cognitive ability

Abstract: The present experiments explored various measures of English and Spanish language ability and compared monolingual and bilingual subjects on tests of cognitive skill. Language ability was assessed in Experiment 1. These measures were found to be highly correlated with each other, with at least two factors needed to describe the associations among the tests in each language. In Experiment 2, subjects were given tests of cognitive skill. To be included in this study, all subjects were required to show adequate u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 29 publications
(32 reference statements)
2
34
0
Order By: Relevance
“…with their monolingual peers living in Iran and found greater performance in measure of originality and fluid intelligence for bilinguals. However, these and similar studies in the field suffer from a serious drawback which is ignoring the bilinguals' developmental factors such as the age of L2 acquisition, the conditions under which the L2 was acquired, the degree of proficiency in L2 (Lemmon, & Goggin, 1989, cited in Kharkhurin, 2011). Birman, Trickett, and vinokurov (2002 believed that "language acquisition is often accompanied by adoption of the cultural values of the country in which this language is acquired".…”
Section: Introductionmentioning
confidence: 99%
“…with their monolingual peers living in Iran and found greater performance in measure of originality and fluid intelligence for bilinguals. However, these and similar studies in the field suffer from a serious drawback which is ignoring the bilinguals' developmental factors such as the age of L2 acquisition, the conditions under which the L2 was acquired, the degree of proficiency in L2 (Lemmon, & Goggin, 1989, cited in Kharkhurin, 2011). Birman, Trickett, and vinokurov (2002 believed that "language acquisition is often accompanied by adoption of the cultural values of the country in which this language is acquired".…”
Section: Introductionmentioning
confidence: 99%
“…They further argue, as many others (e.g. Delgado et al 1999;Dö rnyei 2007;Lemmon and Goggin 1989;McKinney and Priestly 2004), that, methodologically, the heavy reliance on questionnaires leads to a number of problems, including the distillation of complex issues and experiences into a limited number of assessable constructs; the assumption that all informants will equally understand and engage with the concepts/constructs assessed via a questionnaire (e.g. equally 'understanding' references to 'culture', 'identity'); and the 'over-reliance' on subjective evaluations, which may not reflect actual performance or account for the variables which influence language use in reality (e.g.…”
Section: 'Identity' As a Key Variablementioning
confidence: 67%
“…6) Earlier studies that indicated negative consequences of bilingual education include : Arsenian (1937), Graham (1925), Mead (1927), Saer (1923. 7) For instance, Balkan (1970) on Switzerland, Ben-Zeev (1972, 1977 on Israel and New York, Cummins (1978), Feldman andShen (1970), lanco-Worrall (1972) on South Africa, Landry (1974), Lemmon and Goggin (1989) on English and Spanish, Liedtke andNelson (1968), Miller (1983), Scott (1973) on Montreal, Torrance et al (1970) on Singapore and Wagner, Spratt, and Ezzaki (1989) on Morocco. 8) The reasons for this is discussed earlier in note 1.…”
Section: Resultsmentioning
confidence: 99%